Physicochemical characterization of representative firewood species used for cooking in some colombian regions (2017)
ABSTRACT: Socioeconomic conditions and the main firewood species used for cooking in three Colombian regions are studied in this work. The species collected were Cordia alliodora, Guazuma ulmifolia, Eucalyptus grandis, and Pinus patula. The used patterns of biomass and socioeconomic conditions of the selected regions were defined by means of secondary information. Firewood was physicochemically characterized and the species are compared with fossil fuels with regard to emissions of CO2, energy density, and costs. The studied regions require solutions to use firewood in eco-efficient systems, since in these rural regions people use biomass as an energy source. Studied firewood species are suitable to be gasified in fixed bed reactors due to their high volatile matter content (>80%) and low ash content (<1.8%). Pinus patula is the one with the highest fuel value index, mainly due to its low ash content (0.4%). The firewood consumption in advanced stoves has environmental advantages resulting from its low CO2 emissions: a cubic meter of Eucalyptus could replace 113 liters of kerosene or 120 m3 of natural gas for cooking application.